2013
DOI: 10.1080/00268976.2013.793845
|View full text |Cite
|
Sign up to set email alerts
|

On the origin independence of the Verdet tensor

Abstract: The condition for invariance under a translation of the coordinate system of the Verdet tensor and the Verdet constant, calculated via quantum chemical methods using gaugeless basis sets, is expressed by a vanishing sum rule involving a third-rank polar tensor. The sum rule is, in principle, satisfied only in the ideal case of optimal variational electronic wavefunctions. In general, it is not fulfilled in non-variational calculations and variational calculations allowing for the algebraic approximation, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…, is independent of the origin of the laboratory coordinate system, and it is the unique measurable quantity in a disordered medium containing freely tumbling optically active molecules. The separate components, diagonal and off‐diagonal, depend on the origin, and consequently they could not, in principle, be experimentally determined in a molecular crystal. However, diagonal components invariant under a translation of coordinate system can be formally defined allowing for Eq.…”
Section: Translation Of Frequency‐dependent Response Tensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…, is independent of the origin of the laboratory coordinate system, and it is the unique measurable quantity in a disordered medium containing freely tumbling optically active molecules. The separate components, diagonal and off‐diagonal, depend on the origin, and consequently they could not, in principle, be experimentally determined in a molecular crystal. However, diagonal components invariant under a translation of coordinate system can be formally defined allowing for Eq.…”
Section: Translation Of Frequency‐dependent Response Tensorsmentioning
confidence: 99%
“…Within the dipole velocity‐angular momentum gauge ( P , L ), the mixed electric‐magnetic dipole polarizability (MEMDP) tensor is given by καβ(PL)(ω)=e22me2jupdiagonalstrike=a2ωωjatrue(ωja2ω2true)true(true〈a|trueP̂α|jtrue〉true〈j|trueL̂β|atrue〉true), and the equation for its change in a coordinate translation, Eq. , is καβ(P,L)(bold-italicr)=καβ(P,L)(bold-italicr)ω2εβγδααγ(P,P)dδ, where the dynamic electric dipole polarizability within the dipole velocity gauge ( P , P ), ααβ(P,P)(ω)=e2me2ja2ωjatrue(ωja2ω2true)true(true〈a|trueP̂α|jtrue〉true〈j…”
Section: Translation Of Frequency‐dependent Response Tensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In oriented molecules, ϕ has been shown to depend also on Aα,βγ, the mixed electric dipole‐electric quadrupole polarizability (MEDQP), via an origin‐independent combination of terms which separately depend on the origin . At a given frequency ω of the incident monochromatic light, the change of the individual καβ(ω;ω) and Aα,βγ(ω;ω) components in a translation of the origin is described by equations involving the dynamic electric dipole polarizability (EDP), ααβ(ω;ω), at the same frequency . However, it was recently observed that the diagonal components of the MEMDP tensor become translationally invariant if it is referred to the coordinate frame of the eigenvectors of EDP .…”
Section: Introductionmentioning
confidence: 99%